Flow: the psychology of optimal experience - Csikszentmihalyi, Mihaly (New York HarperCollins, 2008)
It teaches how, by ordering the information that enters our consciousness, we can discover true happiness, unlock our potential, and greatly improve the quality of our lives.
Keywords: Psychology